Effect of calcium hydroxide on bacterial endotoxin in vivo - Silva, Léa Assed Bezerra; Nelson-Filho, Paulo; Leonardo, Mário Roberto; Rossi, Marcos A.; Pansani, Cyneu Aguiar (Wolters Kluwer, 2002)
The aim of this study was the histopathological evaluation of apical and periapical tissues in dog teeth that were submitted to bacterial endotoxin, associated or not with calcium hydroxide. After removal of the pulp from 60 premolars, the teeth were divided into four groups and were filled with bacterial endotoxin (group 1), bacterial endotoxin plus calcium hydroxide (group 2), saline solution (group 3), or had induced periapical lesions with no treatment (group 4). After 30 days, animals were killed and the teeth processed histologically. The inflammatory infiltrate, the thickness of the periodontal ligament, and the presence of resorption areas were similar for groups 1 and 4. Groups 2 and 3 were similar to each other. It can be concluded that the bacterial endotoxin caused a periapical lesion and that calcium hydroxide detoxified the lipopolysaccharides in vivo. Copyright © 2002 by The American Association of Endodontists.